Awareness, Integration and Interconnectedness: Contemplative Practices of Higher Education Professionals. (April 2015) - Beer, Laura E.; Rodriguez, Katrina; Taylor, Christina; Martinez-Jones, Naomi; Griffin, Jennifer; Smith, Tony R.; Lamar, Margaret; Anaya, Reyna
Contemplative practices support transformative learning processes but can be difficult to identify in a higher education environment. Advocates of contemplative approaches to education see this void as a concern. When topics like these are ignored, especially when desired by students, staff, and faculty, the holistic, transformative, and deep learning needs of students are unfulfilled. Attention needs to be brought to the connections between contemplative practices and the pursuit of transformative education. In this qualitative study, 17 higher education professionals were asked how they integrate contemplative practices into their work and personal lives. In analyzing the data, three themes emerged, namely, awareness, integration, and interconnectedness. These themes, with accompanying stories, highlight the value and benefits of incorporating contemplative practices into a higher education setting. Using an inductive approach, suggestions for implementing practices were identified and are offered here.